Bridging mRNA and Polycation Using RNA Oligonucleotide Derivatives Improves the Robustness of Polyplex Micelles for Efficient mRNA Delivery. Issue 9 (23rd December 2021) - Yoshinaga, Naoto; Uchida, Satoshi; Dirisala, Anjaneyulu; Naito, Mitsuru; Koji, Kyoko; Osada, Kensuke; Cabral, Horacio; Kataoka, Kazunori
Abstract: Polyplex for messenger RNA (mRNA) delivery requires strong yet reversible association between mRNA and polycation for extracellular robustness and selective intracellular disintegration. Herein, RNA oligonucleotide (OligoRNA) derivatives that bridge mRNA and polycation are developed to stabilize polyplex micelles (PMs). A set of the OligoRNAs introduced with a polyol moiety in their 5′ end is designed to hybridize to fixed positions along mRNA strand. After PM preparation from the hybridized mRNA and poly(ethylene glycol)‐polycation block copolymer derived with phenylboronic acid (PBA) moieties in its cationic segment, PBA moieties form reversible phenylboronate ester linkages with a polyol moiety at 5′ end of OligoRNAs and a diol moiety at their 3′ end ribose, in the PM core. The OligoRNAs work as a node to bridge ionically complexed mRNA and polycation, thereby improving PM stability against polyion exchange reaction and ribonuclease attack in extracellular environment. After cellular uptake, intracellular high concentration of adenosine triphosphate triggers the cleavage of phenylboronate ester linkages, resulting in mRNA release from PM. Ultimately, the PM provides efficient mRNA introduction in cultured cells and mouse lungs after intratracheal administration, demonstrating the potential of the bridging strategy in polyplex‐based mRNA delivery. Abstract : Messenger RNA (mRNA) and polycation are bridged inside polyplex micelle (PM) using RNA oligonucleotide (OligoRNA) derivatives. OligoRNAs hybridize to mRNA via side chain complementary bases, and diol/polyol moieties at both ends of OligoRNAs bind to phenylboronic acid moieties installed in polycation. This strategy improves PM stability against nuclease and polyanions, thereby providing efficient mRNA introduction in vitro and in vivo.